(untitled) (Jurnal Riset Veteriner Indonesia (Journal of The Indonesian Veterinary Research), 2024)
• evansi is a blood parasite that is responsible for the occurrence of surra disease or also known as trypanosomiasis. The T. evansi cells are able to be damaged by the Allicin content of garlic. In the kidney itself, the parts that affect in the case of infection are namely tubules and glomerulus and can be identified through histopathology inspection by taking into account the level of damage. This research is aimed at studying the figure of mice kidney histopathology (M. musculus) that has been being infected by T. evansi and being distributed by garlic extract (A. sativum) with graded dose then compared to the distribution of commercial drug Tryponil. The samples used in this study were 30 mice with 6 treatment groups. P0 group was not infected by T. evansi, P1 group was infected by T. evansi without treatment, P2, P3, and P4 group respectively were infected by T. evansi and distributed garlic extract with 1,4 mg, 2,8 mg, and 5,6 doses respectively. In other hand, P5 group was distributed commercial drug namely Tryponil. The extraction method was through maserasi method. The distribution of the treatment was done in 3 days, euthanized and necropsied on mice in the purpose of organ harvesting for histology sampling with embedding method, blocking, and hematoxylin eosin coloring. The results showed that the closest to the distribution of commercial drug was the distribution of 5,6 mg dose (high dose), where both the treatments showed the result that the damage was not much, then followed by the distribution of 2,8 mg dose (fair dose) and 1,4 mg dose (light dose).